KINERJA KEUANGAN DAN EFISIENSI PROSES INTERNAL SEBELUM DAN SESUDAH PENERAPAN PPK-BLUD PADA RSUD KAB.KLUNGKUNG - Susandi, Nyoman Trio; Budiartha, I Ketut; Suprasto, Herkulanus Bambang (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2017)
This research was conducted at the Rumah Sakit Umum Daerah (RSUD) Kabupaten Klungkung as one of the Satuan Kerja Perangkat Daerah (SKPD) that have implemented Pola Pengelolaan Keuangan Badan Layanan Umum Daerah (PPK-BLUD). This study examined the differences in performance of  RSUD Kabupaten Klungkung before and after becoming PPK-BLUDs. This study uses secondary data such as financial performance and performance efficiency of internal processes, proxied by the performance of revenues, expenses, curent ratio, cash ratio, quick ratio, Bed Occupancy Ratio (BOR), Average Length of Stay (ALOS), Turn Over Interval ( TOI) and Bed Turn Over (BTO). Statistical testing using non-parametric statistical test of Kolmogorov-Smirnov, if the data is normally distributed then followed by paired sample t-test on each variable. The Results of testing the entire proxy using the Test paired sample t-test showed there was no difference of financial performance and the efficiency of internal processes before and after the implementation of the CO-BLUDs. This was caused by RSUD Kabupaten Klungkung management that has not been optimally implement the regulations set out in the Permendagri No. 61 st on 2007.
Keywords: financial performance, efficiency of internal processes performance, PPK-BLUD.